A Comparative Study: Change Detection and Querying Dynamic XML Documents - Vijay R Sonawane; D.R. Rao (International Journal of Electrical and Computer Engineering (IJECE), 2015)
The efficient management of the dynamic XML documents is a complex area of research. The changes and size of the XML documents throughout its lifetime are limitless. Change detection is an important part of version management to identify difference between successive versions of a document. Document content is continuously evolving. Users wanted to be able to query previous versions, query changes in documents, as well as to retrieve a particular document version efficiently. In this paper we provide comprehensive comparative analysis of various control schemes for change detection and querying dynamic XML documents.